Finding Similar Users Using Category-Based Location History - Xiao, Xiangye; Zheng, Yu; Luo, Qiong; Xie, Xing (Proceedings of 18th ACM SIGSPATIAL Conference on Advances in Geographical Information Systems, 2010)
In this paper, we aim to estimate the similarity between users according to their GPS trajectories. Our approach first models a user’s GPS trajectories with a semantic location history (SLH), e.g., shopping malls  restaurants  cinemas. Then, we measure the similarity between different users’ SLHs by using our maximal travel match (MTM) algorithm. The advantage of our approach lies in two aspects. First, SLH carries more semantic meanings of a user’s interests beyond low-level geographic positions. Second, our approach can estimate the similarity between two users without overlaps in the geographic spaces, e.g., people living in different cities. We evaluate our method based on a real-world GPS dataset collected by 109 users in a period of 1 year. As a result, SLH-MTM outperforms the related works [4].